Mechanisms of Resistance to CDK4/6 Inhibitors: Potential Implications and Biomarkers for Clinical Practice - McCartney, Amelia; Migliaccio, Ilenia; Bonechi, Martina; Biagioni, Chiara; Romagnoli, Dario; De Luca, Francesca; Galardi, Francesca; Risi, Emanuela; De Santo, Irene; Benelli, Matteo; Malorni, Luca; Di Leo, Angelo (Frontiers in Oncology, 2019)
The recent arrival of CDK4/6 inhibitor agents, with an approximate doubling of progression-free survival associated with their use in hormone receptor-positive, HER2-negative advanced breast cancer, has radically changed the approach to managing this disease. However, resistance to CDK4/6 inhibitors is considered a near-inevitability in most patients. Mechanisms of resistance to these agents are multifactorial, and research in this field is still evolving. Biomarkers with the ability to identify early resistance, or to predict the likelihood of successful treatment using CDK4/6 inhibitors are yet to be identified, and represent an area of unmet clinical need. Here we present selected mechanisms of resistance to CDK4/6 inhibitors, largely focussing on roles of Rb, cyclin E1 and the PIK3CA pathway, with discussion of associated biomarkers which have been investigated and applied in recent pre-clinical and clinical studies. These biological drivers may furthermore influence clinical treatment strategies adopted beyond CDK4/6 resistance.